2017
DOI: 10.1088/1361-6560/aa73cc
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of outcomes following definitive chemoradiotherapy for oropharyngeal cancer based on FDG-PET image characteristics

Abstract: In this study, we investigate the use of imaging feature-based outcomes research (“radiomics”) combined with machine learning techniques to develop robust predictive models for the risk of all-cause mortality (ACM), local failure (LF), and distant metastasis (DM) following definitive chemoradiation therapy (CRT). One hundred seventy four patients with stage III-IV oropharyngeal cancer (OC) treated at our institution with CRT with retrievable pre- and post-treatment 18F-fluorodeoxyglucose positron emission tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 61 publications
1
58
0
1
Order By: Relevance
“…The model has an AUC of 0.72 (95% CI 0.65-0.79). This is considered to be moderate and is comparable to prediction models from other clinical disciplines with an AUC range from 0.54 to 0.73 [22,23]. Bear in mind that the model is used for prediction of future events, compared to diagnostic models that estimate the probability of the presence or absence of an outcome in the present time.…”
Section: Discussionmentioning
confidence: 81%
“…The model has an AUC of 0.72 (95% CI 0.65-0.79). This is considered to be moderate and is comparable to prediction models from other clinical disciplines with an AUC range from 0.54 to 0.73 [22,23]. Bear in mind that the model is used for prediction of future events, compared to diagnostic models that estimate the probability of the presence or absence of an outcome in the present time.…”
Section: Discussionmentioning
confidence: 81%
“…Such features correlate with clinical outcome and convey medically meaningful information describing tumor heterogeneity, microenvironment, pathophysiology, and mutational burden [13,18,19]. While prior studies demonstrated prognostic value of radiomics biomarkers in head and neck cancers [15,16,[20][21][22][23][24][25][26][27][28], none have incorporated or compared the AJCC 8th edition staging scheme in OPSCC survival modelling and stratification. In this study, we explored the potential added value of radiomics biomarkers in prognostication of PFS and OS-beyond the AJCC staging scheme-in a multi-institutional cohort.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to Participants , the three most recent studies used high‐stage patients and the rest considered any degree of severity. It should also be noted that four studies used external validation cohorts after having previously internally validated the models developed . Finally, one of the studies did not include treatment as a candidate predictor .…”
Section: Resultsmentioning
confidence: 99%